Elevation gradients alter vegetation attributes in mountain ecosystems of eastern Himalaya, India - Negi, Vikram S.; Pandey, Aseesh; Singh, Ajay; Bahukhandi, Amit; Pharswan, Dalbeer S.; Gaira, K. S.; Wani, Zishan Ahmad; Bhat, Jahangeer A.; Siddiqui, Sazada; Yassin, Habab M. (Frontiers in Forests and Global Change, 2024)
The present study describes how vegetation (the tree layer) is shaped along the elevation gradients in the eastern part of the Indian Himalayan Region. Various vegetation attributes, distribution, population structure, and regeneration patterns of 75 tree species belonging to 31 families were studied. Tree species richness shows a low plateau (peaked between 1,300–1,500 m) with a linearly decreasing pattern above 1,500 m asl. Ericaceae was found as the dominant family, followed by Lauraceae and Rosaceae. The distributional pattern of species-to-genera ratio (S/G) did not follow any particular trends, while β-diversity increased along the elevation gradient. The Margalef index of species richness, the Menheink index of species richness, and the Fisher alpha were found to be highest at lower altitudes (1,000–1,500 m), while the Simpson index was highest at middle altitudes (2,600–3,000 m). Random distribution was shown by maximum tree species (47.3%), followed by a contagious distribution (42.9%), and regular distribution (10.8%). The regeneration of tree species was found to be good with a healthier number of seedlings (10.2%), fair (43.5%), poor (30.3%), while 16% were observed not regenerating. Acer laevigatum (1,500 m), Prunus nepalensis (3,300 m), Viburnum sympodiale (3,400 m) were among the new regenerating species at the respective altitudes. The population structure of tree species in terms of proportion of individuals in seedlings, saplings, and the adult class varied in all the elevation transects. Species with better regeneration on upper distribution limits have been recognized as probable for upward movement.